Psychology of religion in Turkey - Ağilkaya-Şahin, Zuhâl.; Streib, Heinz, 1951-; Ayten, Ali.; Hood, Ralph W., Jr., 1942- (Religious Studies, Theology and Philosophy E-Books Online, Collection 2015, ISBN: 9789004287471., 2015)
In Psychology of Religion in Turkey , senior and emerging Turkish scholars present critical conceptual analyses and empirical studies devoted to psychology of religion in Turkey. Part 1 consists of articles placing the psychology of religion in the historical context of an ancient culture undergoing modernization and secularization and articles devoted to conceptual themes suggesting the uniqueness of Islam among the great faith traditions. Part 2 is devoted to empirical studies of religion in the Turkish-Islamic includuing studies focused on the religious life of Turkish youth, popular religiosity, spirituality, and Muslim religious development in light of Al-Ghazzali. Part 3 is devoted to several empirical studies on a variety of social outcomes of religious commitment in Turkey.